ECMS 2016 Proceedings Edited by Thorsten Claus, Frank Herrmann, Michael Manitz, Oliver Rose 2016
DOI: 10.7148/2016-0159
|View full text |Cite
|
Sign up to set email alerts
|

The Use Of Cluster Analysis For Demographic Policy Development: Evidence From Russia

Abstract: Russia has been experiencing a demographic crisis since the 1990s. The most obvious manifestations include an excess of mortality over fertility rates, population decline and an ageing population. The last 20 years have seen considerable activity to come up with new demographic policy measures to mitigate these adverse trends, with single solutions developed for all regions in Russia. This paper presents the results of a study where cluster analysis was applied to enable the identification of groups of regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…We have previously demonstrated the profiling of these clusters and the assessment of the statistical significance of the obtained model of Russia's demographic space (Shubat et al 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated the profiling of these clusters and the assessment of the statistical significance of the obtained model of Russia's demographic space (Shubat et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The clustering of Russian regions on the basis of indicators describing the conditions for the formation of demographic potential at the macro-level -that is, the regional level (Study 1) -was based on the following variables:  Birth rate;  Perinatal mortality rate;  Infant mortality rate;  Under-five mortality rate;  Pregnancy rate. We presented the results of this clustering previously (Shubat et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the differentiation of Russian regions was not taken into consideration, which fully negated the possible impact of introducing the maternity capital programme. For example, our earlier research showed that countries with a large number of constituent parts with high variance in their development require a demographic policy that is differentiated by type of region (Shubat et al 2016). Such development of targeted measures for different types of regions would improve the effectiveness of Russia's overall demographic policy.…”
Section: Discussionmentioning
confidence: 99%
“…It is broadly acknowledged that multivariate cluster analysis is an effective analytical tool to carry out regional segmentation (Johnson and Wichern, 2007;Shubat et al, 2007). It is also evident that regional segmentation, i.e., identifying homogeneous (or heterogeneous) groups is an effective and need-based approach for designing and implementing the community-based research.…”
Section: Discussionmentioning
confidence: 99%